Um empreendedor de políticas públicas em ação:Bresser Pereira e a reforma da administração pública de 1995 no Brasil - Leite, Leonardo Queiroz (2014)
This study aims to understand and clarify the role of the former Minister of Federal Administration and State Reform (1995 1998), Luiz Carlos Bresser Pereira, in the strategic position of the main formulator of the public management reform in Brazil. In this sense, we will provide a Reform explanation observing how the political and intellectual construction of this public policy directly derived from the persuasive action Bresser Pereira in exercising the "power of ideas". Here, we consider as essential the structural limits of the Ministry of Federal Administration and State Reform as the fundamental political and institutional locus for the formulation of policy reform. Thus, through the analysis of the profile and policy measures undertaken by the former minister Bresser, according to the theoretical framework adopted, with particular emphasis on the theoretical model of John Kingdon, we verify the existence of a typical policy entrepreneur in action. Therefore, we demonstrate that Bresser Pereira exercised the intellectual and political leadership at the time of construction and dissemination of the main principles of the o called "New Public Management" in Brazil, supporting the reform policy of the first Fernando Henrique Cardoso s administration. Our focus on the performance and characteristic profile of the chosen entrepreneur reveals that the individual action of the actors is an important dimension in public policy production process. Thus, we intend to contribute to enrich the academic production in the field of political science and its intersection with the area of public policy, filling analytical gaps about the performance of policy entrepreneurs, providing a new theoretical and empirical analysis research about the State Reform in Brazil.